Combined hyperthermia and radiotherapy for prostate cancer: a systematic review. (31st December 2022) - Le Guevelou, Jennifer; Chirila, Monica Emilia; Achard, Vérane; Guillemin, Pauline Coralie; Lorton, Orane; Uiterwijk, Johannes W. E.; Dipasquale, Giovanna; Salomir, Rares; Zilli, Thomas
Abstract: Optimization of treatment strategies for prostate cancer patients treated with curative radiation therapy (RT) represents one of the major challenges for the radiation oncologist. Dose escalation or combination of RT with systemic therapies is used to improve tumor control in patients with unfavorable prostate cancer, at the risk of increasing rates and severity of treatment-related toxicities. Elevation of temperature to a supra-physiological level has been shown to both increase tumor oxygenation and reduce DNA repair capabilities. Thus, hyperthermia (HT) combined with RT represents a compelling treatment strategy to improve the therapeutic ratio in prostate cancer patients. The aim of the present systematic review is to report on preclinical and clinical evidence supporting the combination of HT and RT for prostate cancer, discussing future applications and developments of this combined treatment.